Penerapan Manajemen Risiko dalam Mengurangi Infeksi Pelayanan Kesehatan di Rumah Sakit Kota Yogyakarta - Totok Sundoro (LPPM Akademi Manajemen Administrasi Yogyakarta, 2026)
Nosocomial infections remain a major challenge for hospitals because they can increase morbidity, mortality, treatment costs, and patient length of stay. Effective infection prevention and control are therefore essential to improve patient safety and healthcare quality. This study aimed to examine risk management practices for infection prevention at Yogyakarta City Hospital. A qualitative study with a phenomenological approach was employed. Informants included hospital management, healthcare staff, and patients selected through purposive sampling. Data were collected through interviews, observations, documentation, and simulations. The findings indicate that the hospital has implemented comprehensive infection risk management through policies and standard operating procedures, hand hygiene programs, personal protective equipment (PPE) use, environmental disinfection practices, airborne isolation facilities, waste management systems, and continuous program evaluation. The study concludes that effective infection risk reduction can be achieved through strong institutional policies, structured infection control programs, dedicated program management, and ongoing staff education and training to ensure compliance with patient safety standards.